Compensatory Upregulation of Anti-Beta-Adrenergic Receptor Antibody Levels Might Prevent Heart Failure Presentation in Pediatric Myocarditis - Seidel, Franziska; Scheibenbogen, Carmen; Heidecke, Harald; Opgen-Rhein, Bernd; Pickardt, Thomas; Klingel, Karin; Berger, Felix; Messroghli, Daniel; Schubert, Stephan (Frontiers in Pediatrics, 2022)
Background Myocarditis can be associated with severe heart failure and caused by different inflammatory and autoimmune responses. The aim was to describe the immunological response in children with myocarditis by analyzing anti-beta-adrenergic receptor antibodies (anti-β-AR Ab). Methods Sera of children hospitalized with biopsy-proven myocarditis were prospectively collected between April 2017 and March 2019. Anti-β1-AR Ab, anti-β2-AR Ab and anti-β3-AR Ab were quantified by a CE-certified ELISA kit. According to normal values for immunoglobulin G three age groups <1year, 1-5years and >5-17years were defined. Children without inflammatory cardiac pathology and no heart failure signs served as a control group. Results We compared 22 patients with biopsy-proven myocarditis and 28 controls. The median age (interquartile range) of the myocarditis group was 12.1 (2.7-16.4) years, 13 male, left ventricular ejection fraction (LVEF) 51%; controls: 5.0 (3.0-6.8) years, 9 male, LVEF 64%. Myocarditis patients in the age group >5-17years showed significantly higher anti-β3-AR Ab levels compared to controls (p=0.014). Lower anti-β2-AR Ab and anti-β3-AR Ab levels were significantly correlated with higher left ventricular diameters in myocarditis patients. The event-free survival using a combined endpoint (mechanical circulatory support, transplantation and/or death) was significantly lower in myocarditis patients with antibody levels below the median compared to myocarditis patients with antibody levels ≥ median. Conclusion Anti-β-AR Ab levels are elevated in children with myocarditis and >5 years of age. These antibodies might be upregulated compensatory to prevent further cardiac deterioration. A worse event-free survival in patients with lower anti-β-AR Ab levels might be a therapeutic target for immunoglobulin substitution.